Remote Working: Examining Benefits, Challenges and Organizational Practices - Makkar, Mansi; Rani, Neetu (PT FORMOSA CENDEKIA GLOBAL, 2024)
In 2020, during COVID-19 pandemic, to maintain the smooth flow of work and reduce the chance of getting infected and transmitting the virus, businesses had no choice but to shut down the offices and adapt remote working. The development of information and communication technologies has made it possible for workers to work remotely without much difficulty. Like everything, working from home has upsides and downsides of its own. Thus, the objective of this study was to describe the benefits of remote working along with the challenges that comes with it. With the help of existing literature, the study also identified organizational practices that will improve the experience of remote working for employees. The research finds that setting clear goals, use of appropriate communication tools, establish clear remote work policies and norms, flexibility, timely performance assessment and feedback, and mental health assistance enhances the successful implementation and employee’s experience in remote working.